2020
DOI: 10.1097/md.0000000000023405
|View full text |Cite
|
Sign up to set email alerts
|

Imaging characteristics of Intrasellar cavernous hemangioma

Abstract: Rationale: Intrasellar cavernous hemangiomas (ICHs) are rare vascular lesions that arise in the sellar region. ICHs are usually misdiagnosed and treated as pituitary adenomas. Therefore, a preoperative diagnosis is particularly important, especially when the goal is complete resection. Patient concerns: A 55-year-old woman presented with a 1-month history of intermittent dizziness. Magnetic resonance imaging (MRI) revealed a well-demarcated abnormal ell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, in the literature, some MRI features have been reported that could raise the suspicion of CM of the sellar region. Indeed, the presence of a hyperintense signal in T2 sequences associated with delayed centripetal contrast enhancement on MRI images could raise suspicion ( 39 ). Due to the high vascularity and profuse bleeding of the lesion during surgical removal, a subtotal resection to obtain neurovascular decompression followed by radiotherapy might be considered the most effective strategy of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the literature, some MRI features have been reported that could raise the suspicion of CM of the sellar region. Indeed, the presence of a hyperintense signal in T2 sequences associated with delayed centripetal contrast enhancement on MRI images could raise suspicion ( 39 ). Due to the high vascularity and profuse bleeding of the lesion during surgical removal, a subtotal resection to obtain neurovascular decompression followed by radiotherapy might be considered the most effective strategy of treatment.…”
Section: Discussionmentioning
confidence: 99%